Ticking the ethnic box: minority young in rural communities. - Philomena de Lima; Norma Hart (University of Aberdeen, School of Education, 2016)
Continuing on the theme of inclusion, my second choice of paper advocates a more inclusive approach in relation to identities of minority ethnic young people in rural Scotland. I believe the paper makes an important contribution to the debate on ethnicity and identity, highlighting the need to challenge the tendency to conflate ethnicity and ethnic minorities with non-white and the important role to be played by schools.